PROTOTIPE SISTEM PENGUKURAN LAJU KENDARAAN BERMOTOR SEBAGAI UPAYA PENGAWASAN TERHADAP PELANGGARAN RAMBU-RAMBU LALU LINTAS - Nandang Kuswandi; Frida Agung Rakhmadi (Integrated Lab Journal, 2018)
The research on measure system prototype of speed motor vehicle measurement system as surveillance effort of infringement on traffic signs has been done. The research aimed to create a prototype a speed measurement system that can be applied to measure the speed of vehicles on the road. Phases of the research contains of making prototypes which includes the manufacture of hardware and software, prototype testing which consists of a characterization of the output voltage of detector, test of accuracy and precision, and data processing test results. The test results of the output voltage detector readings obtained from ADC value mikrokontoler Arduino Uno. ADC value when conditions hindered was ≥ 813 and when the detector was exposed to laser light was ≤ 91. Meanwhile, the accuracy of test results on the prototype obtained a value of 99.938% and a precision test of 95%.